EVALUASI DAN OPTIMASI EFISIENSI ENERGI SISTEM CHILLER DENGAN PROSES DESCALING - M. Nuriyadi; Ade S. Margana (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2019)
Chiller system consumes most energy (around 50%) of the electrical energy in a building. To reduce the use of energy, it is necessary to evaluate the use of energy and identify opportunities for energy savings and recommendations for increasing efficiency. The evaluation aims to ensure that a chiller system works and produces chilled water products as designed. The chiller system evaluation includes the evaluation of the chiller refrigeration system, power consumption, cooling capacity, as well as the evaluation of the piping system and pumps. Evaluation is carried out on the system before and after repairing/descaling on the chiller system. The results of the evaluation and optimization of the chiller system are: the chilled water temperature output drops to 15oC, the cooling capacity of the chiller rises to 30 KW, the pressure of the condenser coolant pump rises to 0.58 bar. While the efficiency of the circulating pump system is 15.8%; efficiency of condenser cooling pump is 19.3% and distribution pump system efficiency is 14.1%. Keywords: performance evaluation, optimization, chiller system.